Suppression of an unwanted flow of charged particles in a tandem accelerator with vacuum insulation. (13th April 2016) - Ivanov, A.; Kasatov, D.; Koshkarev, A.; Makarov, A.; Ostreinov, Yu.; Shchudlo, I.; Sorokin, I.; Taskaev, S.
Abstract: In the construction of a tandem accelerator with vacuum insulation several changes were made. This allowed us to suppress the unwanted flow of charged particles in the accelerator, to improve its high-voltage stability, and to increase the proton beam current from 1.6 mA to 5 mA.